Towards a new type of heterometallic system based on a paddle-wheel Ru2 dimer: first results derived from the use of a high spin diruthenium(iii, iii) building block. Issue 6 (11th May 2017) - Yang, Bing-Bing; Feng, Li-Na; Fan, Xiao-Meng; Zhang, Kai-Xiang; Yang, Jian-Hui; Liu, Bin
Abstract : Heterometallic diruthenium(iii, iii ) compound shows a two-step relaxation and order below 14 K with a coercive field of 24.9 kOe at 1.8 K. Abstract : A new facile strategy has been reported for the synthesis of homovalent diruthenium(iii, iii ) phosphates. On assembling the homovalent Ru2 units and Cu 2+ in the presence of K +, new trimetallic phosphates, K2 [Cu(H2 O)2 Ru2 (PO4 )4 (H2 O)2 ] (1 ), were formed. In compound1, the Ru2 dimer showed a Ru–Ru double bond distance of 2.3400 Å with a high spin ground state S = 2, and neighboring [Ru2 (PO4 )4 (H2 O)2 ] 6− units were linked via distorted tetragonal pyramid Cu(H2 O) 2+ ions, forming the negative layer [Cu(H2 O)2 Ru2 (PO4 )4 (H2 O)2 ] n 2 n − . Antiferromagnetic coupling was mediated between Ru2 6+ and Cu 2+ via O–P–O bridges. Detailed magnetism measurements demonstrated that compound1 exhibited a two-step relaxation in oscillation susceptibilities, and an order below 14 K with a large coercive field of H c = 24.9 kOe at 1.8 K. It is the highest T c and H c for the non-carboxylate diruthenium compounds reported to date.